PEMANFAATAN REDMINE, SUBVERSION DAN HAMACHI SEBAGAI MANAJEMEN PROYEK SISTEM INFORMASI PADA JARINGAN VPN - Muhammad Sony Maulana (Paradigma, 2012)
Managing a project has a challenge for a project manager should be able to utilize existing resources and look at the rules and restrictions that need attention. Cooperation among the team would also have to coordinate the project manager so that all team members have the same mission and vision. The development of information technology is now offering a way of virtualteam work, teamwork is not influenced by the geographic location where the inter-team is located. Redmine is a software application as a project manager tool to manage resources. Redmine application is a web-based applications that can be accessed by anyone using a browser on the same network. Internet today opens an opportunity for anyone able to transact with each other indifferent parts of the world's data, so that when the application Redmine is on the Internet network so anyone can access the application anywhere as long as users are connected on the Internet. Web-based application that is placed on the Internet network would be accessible by anyone. Implementation of web applications on the Internet network to be accessible by a team would alsohave to use the Internet, and how web-based applications can be accessed by anyone on the Internet without using a Public IP. Hamachi is a VPN client application that can be utilized as a liaison computers that have connected to the Internet network and who do not have a Public IP so that any computer connected to the Hamachi network can be like an intranet network.Keywords : Redmine, VPN, Hamachi, Subversion, Project Management